(untitled) (Journal of Bio-Science, 2009)
The duration of developmental stages of Tetranychus urticae Koch was studied in different months of a year at room temperature. In addition fecundity of this mite was also observed in winter, autumn and summer seasons. T. urticae eggs hatched to larvae in the shortest duration of 1.07 ± 0.26 days and the longest duration of 11.67 ± 2.33 days in April and January, respectively. The larval period of T. urticae took the shortest time of 0.55 ± 0.50 days in May and 2.93 ± 1.07 days in December. The protonymph transformed to deutonymph in 0.89 ± 0.32 day in May and 3.71 ± 1.94 in December and January. The deutonymph required the shortest duration of 0.92 ± 0.41 days in August and the longest of 10.26 ± 1.48 days in January. The temperature played significant (P<0.001) role on the duration of developmental stages of T. urticae. The high temperature accelerated the developmental rate and reduced the duration of developmental periods. Its life cycle completed within 4.22 ± 0.46 days at 28.53 ± 3.17°C but 28.33 ± 2.36 days at 13.78 ± 2.36°C. A female T. urticae deposited 82.46 ± 4.11 eggs in autumn, 62.96 ± 12.09 eggs in summer and 58.21 ±1 3.65 eggs in winter. Key words: Developmental stages, Tetranychus urticae, temperature, fecundity DOI:10.3329/jbs.v16i0.3751 J. bio-sci. 16: 109-114, 2008